Mirpur Benarasi Palli of Bangladesh: Living and Livelihood of Weavers - Ferdous, Jannatul; Shawal, Shammi; Badhon, Tasfia Tasnim (International Journal of Chemical and Process Engineering Research, 2014)
Bangladesh has a rich and ancient tradition of fabric-based cottage industry. Benarasi Palli and its famous Benarasi Saree is one of the most ancient traditions of Bangladesh. This industry has been bringing name and fame for our country for a very long time. This tradition has mainly come from Benaras in India. The weavers of Mirpur Benarasi Palli migrated from Benaras, India. There are also some Bangladeshi weavers and most of the traders are Bangladeshi. Benarasi is mainly associated for bridal costume. Presently this industry does not get proper attention but it has a great demand in local and international market. Our neighboring country export Benarasi products and we have the potential to export it too. Though the business of Benarasi Saree is very profitable, life-style of the weavers does not represent it. Besides, a clear discrimination in living condition of traders and weavers are visible there. There also lies discrimination in distribution of profit between traders and weavers. So it is very important to know about the present condition of Benarasi Palli and condition of the weavers who work hard to make the beautiful Benerasi Sarees.